Advances in Liver Regeneration: Revisiting Hepatic Stem/Progenitor Cells and Their Origin - Ali-Reza Sadri; Marc G. Jeschke; Saeid Amini-Nik (Hindawi Limited, 2016)
The liver has evolved to become a highly plastic organ with extraordinary regenerative capabilities. What drives liver regeneration is still being debated. Adult liver stem/progenitor cells have been characterized and used to produce functional hepatocytes and biliary cells in vitro. However, in vivo, numerous studies have questioned whether hepatic progenitor cells have a significant role in liver regeneration. Mature hepatocytes have recently been shown to be more plastic than previously believed and give rise to new hepatocytes after acute and chronic injury. In this review, we discuss current knowledge in the field of liver regeneration and the importance of the serotonin pathway as a clinical target for patients with liver dysfunction.